Pengaruh Tax Planning, Thin Capitalization, Profitabilitas, Likuiditas dan Ukuran Perusahaan terhadap Nilai Perusahaan - Puspitasari, Agnes; Suhartono, Sugi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
The purpose of establishing a company is to maximize profits by using existing resources and provide prosperity to shareholders. Firm value can be a benchmark for investors' views of a company's performance, which is usually associated with the size of the share price in the capital market. One of the factors that can affect the value of the company is tax. With the acquisition of large profits, the company is responsible for paying large taxes. To minimize the tax burden paid, companies can carry out tax planning and practice thin capitalization. The company's financial performance can also be a consideration for investment decisions by investors. Therefore, this study aims to examine the effect of tax planning, thin capitalization, profitability, liquidity and company size on firm value. With the sampling technique using purposive sampling, 33 consumer non-cyclicals sector companies were obtained which were listed on the Indonesia Stock Exchange for the 2019-2021 period as research samples. Data analysis techniques and hypothesis testing used were coefficient similarity test, descriptive statistics, classic assumption test (normality, autocorrelation, heteroscedasticity, multicollinearity), multiple linear regression analysis, F test, t test and test of the coefficient of determination using SPSS 26. Conclusions from this research is not proven that tax planning, liquidity and firm size have a positive effect on firm value, but thin capitalization and profitability are proven to have a positive effect on firm value.